Geotechnical and piezoresistivity properties of sustainable cementitious stabilized sand reinforced with recycled fibres - Abedi, Mohammadmahdi (2021)
In this study, the geotechnical and piezoresistivity properties of a sustainable self-sensing cementitious stabilised sand reinforced with recycled fibres (self-sensing cementitious geocomposite, SCG) were extensively investigated. In this route, different concentrations of recycled glass, polypropylene, and ultra-high-molecular-weight polyethylene (GF, PP, and UHMWPE) fibres were incorporated into the conductive stabilised sand with 10% cement composed of 0.17% hybrid (1:1) carbon nanotubes (CNTs) and graphene nanoplatelets (GNPs). The specimens were fabricated using the standard Proctor compaction method at optimum water content, and their mechanical, hydraulic, microstructural, durability, and piezoresistivity properties were investigated after 28 days of hydration using different laboratory test methods. The test results indicate that the maximum dry densities of all SCGs were obtained with a degree of saturation of approximately 85%. For these moisture conditions, there are well-defined relationships between the maximum dry density and strength, permeability, and ultrasonic pulse velocity for SCGs. The GF and UHMWPE fibres exhibited the best performances in terms of strength, durability in climatic cycles, as well as a reduction in permeability. A unique relationship between the ratio of tangent modulus and strength with the strain was defined for all the SCGs that can be of practical use in geocomposite. Furthermore, the piezoresistivity and sensitivity of the SCGs were also increased by reinforcing the geocomposites with fibres, due to increasing their ductility. In summary, we believe that this novel approach contributes to a new era of smart geocomposite materials in sustainable intelligent transport infrastructures.